A NODEMCU INTERNET OF THINGS-BASED FIRE AUTOMATION DESIGN WITH BLYNK APPS NOTIFICATIONS - Rafli Permana; Andrie Yuswanto; Budi Wibowo (TEKNOKOM, 2023)
The impact of fires causes quite large losses, often even causing fatalities. The method used in the system is monitoring the fire sensor which is used to detect a fire, the buzzer as a notification output in the form of sound, and the water pump as a fire extinguisher which will function after the fire sensor is on. detecting the presence of fire. to detect fire in realtime and 9 in the event of a fire with a research and development. Monitoring approach on fire sensors used to detect the presence of fire, buzzers as output notifications in the form of sound, and water pumps as a tool to extinguish fires which will function after the fire sensor detect the presence of fire.